2017
DOI: 10.3390/economies5040049
|View full text |Cite
|
Sign up to set email alerts
|

The Consequences of Corruption on Inflation in Developing Countries: Evidence from Panel Cointegration and Causality Tests

Abstract: Up until the 1980s, studies on corruption were dominated by disciplines of public administration and sociology. In the following years, however, economists have also provided a good amount of research on this issue. According to Transparency International Agency, corruption, which has a negative impact on most macroeconomic indicators, is "the abuse of entrusted power for private gain". Even though the disruption of corruption causing weak growth and investment rates has long been examined, there is little evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
0
15
0
2
Order By: Relevance
“…The other view is that corruption encourages inflation. Some studies in this category include Al-Marhubi (2000) , Piplica (2011) and Ozsahin and Ucler (2017) . By and large, regardless of the line of causation, all the above listed studies unanimously agreed that inflation rate increased with increasing level of corruption.…”
Section: Why Corruption and Inflation Should Be Linkedmentioning
confidence: 99%
“…The other view is that corruption encourages inflation. Some studies in this category include Al-Marhubi (2000) , Piplica (2011) and Ozsahin and Ucler (2017) . By and large, regardless of the line of causation, all the above listed studies unanimously agreed that inflation rate increased with increasing level of corruption.…”
Section: Why Corruption and Inflation Should Be Linkedmentioning
confidence: 99%
“…This is surprising because inflation plays a vital role in the relation among corruption, innovation, and growth. For instance, rising prices, cost overruns, and delayed projects could stimulate bribery across several sectors (Özşahin and Üçler, 2017;Blackburn and Powell, 2011). As the costs of projects rise due to the inflation, firms' funds are negatively impacted leading to reduction in the resources devoted for R&D and, consequently, a slowdown in the country's economic growth in long run (Blackburn and Powell, 2011).…”
Section: Bangladeshmentioning
confidence: 99%
“…The coefficient of import price, was positive meaning that, import prices had positive relation with inflation. By using Johannes cointegration utilizing by [37] found that import of goods and services was the main reason of inflation. The study of [26] is when government expenditure are more than their revenue, the government takes deficit financing, therefore, prices level increases and also inflation occurs.…”
Section: Cost Channel Of Mtmmentioning
confidence: 99%